Sharpening the Health Policy Analytical Rapier; Comment on "The Politics and Analytics of Health Policy" - Martin Powell (Kerman University of Medical Sciences, 2014)
This commentary on the Editorial 'The politics and analytics of health policy' by Professor Calum Paton focuses on two issues. First, it points to the unclear links between ideas, ideology, values, and discourse and policy, and warns that discourse is often a poor guide to enacted policy. Second, it suggests that realism, particularly 'programme theory' are useful tools for health policy analysis. 'Market reform' cannot be reduced to a simple 'four legs good, two legs bad' verdict, and programme theory might suggest that certain mechanisms may be good for one outcome in a particular context, but bad for another.